Rise Up and Walk: Psychology, Comparative Theology, and the Oxford Handbook of Religious Conversion - Locklin, Reid B. (Pastoral psychology, 2018)
This article provides a review and assessment of the Oxford Handbook of Religious Conversion (2014) as a resource for the emerging discipline of comparative theology and, in particular, Hindu-Christian studies. Co-editor Lewis Rambo has highlighted the importance of this volume as an example of a new multi-disciplinary approach to the psychology of religion, one that incorporates the insights of theological studies along with phenomenology of religion, history of religions, and other disciplines. In the vision of the Handbook, however, theology would seem to remain an object of inquiry, as its norms and patterns inform a broader, integrative, social scientific project. The article argues that theology can emerge as a subject as well as an object, opening at least the possibility of a deepened, renewed, and truly constructive comparative inquiry into the phenomenon of religious conversion.